Predicting matrix and delamination fatigue in fiber-reinforced polymer composites using kinetic theory of fracture. (December 2018) - Bhuiyan, Faisal H.; Fertig, Ray S.
Highlights: Matrix cracking and delamination modeled using kinetic theory of fracture (KTF). KTF applied to capture damage of the polymer matrix due to fatigue. Only four parameters required to calibrate the fatigue model. Stiffness degradation of 3 different laminates validated with experimental results. Damage state comparisons at different layers provide good match. Abstract: Prediction of fatigue in fiber-reinforced polymer (FRP) composites demands progressive damage analysis tools that account for constituent physics of the problem. In this work, a matrix fatigue failure methodology based on the kinetic theory of fracture (KTF) is developed that uses the physics of the matrix constituent to track damage in both lamina and interlaminar regions. This model is calibrated from either off-axis lamina or ±45 laminate fatigue tests. Using this methodology, finite element simulations of open-hole coupons comprised of three different laminates subjected to tension-tension fatigue loading are performed. The coupons consist of the unidirectional IM7/977-3 lamina with available calibration and validation data. In this work, both intra-ply matrix cracks and inter-ply delamination mechanisms are simulated. The resultant residual stiffness and the damage accumulation inside the plies due to matrix failure with a specific number of fatigue cycles are benchmarked against published experimental data. The results show good agreement with this data for all three laminates.